Optimal parameters for reagent treatment of Hrybovychi landfill leachates at the pilot-scale treatment plant - Malovanyy, Myroslav; Zhuk, Volodymyr; Tymchuk, Ivan; Sliusar, Vira; Vronska, Nataliya; Marakhovska, Anastasiya; Sereda, Andriy (Ecological Questions, 2022)
Promising technologies for the treatment of solid waste landfill leachates are considered with an emphasis on reagent and combined methods. The purpose of this study was to estimate at the pilot-scale level optimal technological parameters of the leachate oxidation using the modified Fenton process, accompanied by the simultaneous coagulation-flocculation followed by gravitational sedimentation. Pilot-scale leachate treatment plant was installed at the Hrybovychi MSW landfill (Ukraine), and reagent treatment of leachate was a second stage treatment after the aerobic biological pre-treatment. Reagent treatment unit worked in a batch mode, with nominal volume of treated leachate 100 dm3 per cycle. Dependencies of the key pollution indicators (ammonium nitrogen, total Kjeldahl nitrogen, BOD, COD, pH, suspended solids) versus the dosage of reagent solutions are obtained. The optimum specific dosages of reagent solutions are found to be equal: 0.04 m3 of PAA 0.1 wt% solution per 1 m3 of leachate; Al2(SO4)3×18 H2O (10 wt.%) – 0.03–0.04 m3/m3; FeSO4×7H2O (10 wt.%) – 0.06–0.08 m3/m3; hydrogen peroxide (10 wt.%) – 0.04–0.05 m3/m3. High efficiency of COD reduction (88.2–89.5%) is obtained at optimal doses of reagent solutions, and the optimum [H2O2]/COD ratio was found to be 0.23–0.25. Obtained maximum effects of COD reduction significantly exceed corresponding effects for the simple Fenton process reported before. This result could be explained by the synergistic effect of additional flocculation and coagulation immediately before the input of Fenton reagent. Results of the study showed the efficiency of the proposed treatment technology and allow recommending this technology for the implementation at landfill leachate local treatment plants.